Penetapan Kadar Zink dalam Ikan Tongkol yang Beredar di Pasar Sei Sikambing secara Spektrofotometri Sinar Tampak - Muhammad Gunawan; Ucha Gustamayanti (Journal of Indah Science and Clinic, 2020)
Tuna as a seafood product that is often consumed by the public, has a high protein content and omega-3 fatty acids. The micro zinc mineral is needed, both for the synthesis and degradation of biomolecules as well as the role of enhancing the immune system. Zinc reacts with ditizone in a red base. Research to determine zinc content in raw, fried, steamed, and grilled tuna. Samples were taken purposively at the Sei Sikambing Medan traditional market, determination of levels using visible spectrophotometry, digestion with a solution of ditizone in alkaline. Method validation parameters include accuracy, precision, and sensitivity. Percent recovery of 100.50% and RSD 0.95%, LOD 0.620 ?g/ml and LOQ 2.066 ?g/ml. The zinc levels of raw, steamed, fried, and grilled tuna were 22.214 mg, 22.063 mg, 22.3384 mg, and 22.234 mg per 100g, respectively. ANOVA test, there is a significant difference in the acquisition of zinc levels in raw tuna, steamed tuna, grilled tuna, fried tuna. The method used is quite accurate. The zinc content of raw, fried, grilled tuna was higher than that of steamed, but there was no real difference.